Urban Resilience and Planning Support Systems: The Need for Sentience - Deal, Brian (2017)
Developing resilience in built human environments is a complex undertaking. It requires decision support tools that can convey complexities in meaningful and understandable ways. Building smart cities and generating big data, however, is not enough. In order to improve decision-making and ultimately inform resilient communities we need to be able to translate big data at scales and in ways that are useful and approachable. In this paper we argue that creating more resilient communities calls for planning support systems (PSSs) that go beyond the ones we have today. We call for PSSs that possess a greater degree of sentience—that (a) possess a greater awareness of application context and user needs; (b) are capable of iterative learning; (c) are capable of spatial and temporal reasoning; (d) understand rules; and (e) are accessible and interactive. We consider the questions: How might intelligent or sentient information delivery systems allow for more strategic, context-aware, resilient, and ultimately sustainable communities? What primary design considerations would make such a system possible and useful given that, as of yet, no technology exists that is fully “sentient?”